World development report 1978 - World Bank (Washington D.C.: The International Bank for Recontruction and Development/ The World Bank, 1978)
The World Development Report, 1978, along with its statistical annex, is the first of a series of annual reports providing a comprehensive assessment of the global development issues. This first report deals with a number of fundamental problems confronting the developing countries.
rpm 08/02/2019
Ref.
Keywords: Economic development; Power resources; Developing countries